Review of The Magical Properties of Training in the Workshop, by Liv Mjelde (2002), in terms of professional training and work in Latin America - Borjas Borjas, Beatriz
This review aims to approach the validity of the concepts of vocational training and work presented by Liv Mjelde in The magical properties of training in the workshop (2002) in the Latin American context. Especially because the book abounds in contextualizations, we will also try to compare the visions of professional training in Latin environments. The methodology used is based on the exchange of experiences among different research on educational issues, with the dimension of socio-labor insertion, and with a proven track record in gender issues.